Underwater success. (February 2021) - Kouchner, Antoine
Abstract : In response to the news story "Neutrino observatory set for the Pacific Ocean" (October p14) about the planned Pacific Ocean Neutrino Experiment, which, once built by the end of the decade, will be one of the world's largest neutrino telescopes.